Neuropathic pain in Charcot–Marie‐Tooth disease: A clinical and laser‐evoked potential study. (17th February 2022) - Peretti, Alessia; Squintani, Giovanna; Taioli, Federica; Tagliapietra, Matteo; Cavallaro, Tiziana; Fabrizi, Gian M.
Abstract: Background: Pain, either nociceptive or neuropathic (NP), is a common symptom in Charcot–Marie‐Tooth (CMT) disease. Methods: We investigated small fibers involvement and its correlation with pain in different CMT subtypes through a systematic clinical and neurophysiological study. We enrolled 50 patients: 19 with duplication of PMP22 (CMT1A), 11 with mutation of MPZ (CMT1B, CMT2I/J, or CMTDID), 12 with mutation of GJB1 (CMTX1), and 8 with mutation of MFN2 (CMT2A and CMT2A2B). Pain was rated with the 11‐point Numerical Rating Scale and characterized through Neuropathic Pain Symptoms Inventory. Laser‐evoked potentials (LEPs) were recorded after right foot and hand stimulation and N2–P2 complex amplitude and latency were compared with those of 41 controls. Results: Overall pain prevalence was 36%. NP was present in 14.6% of patients, with a length‐dependent distribution in 85.7% of cases, and it was significantly more frequent in CMT1A ( p < 0.001). Aδ fibers involvement greatly varies between CMT subtypes, reflecting differences in molecular pathology and pathophysiologic mechanisms. Prolonged N2 latency from foot stimulation was noted in 11 CMT1A patients, 5 of which report NP. MPZ‐CMTs displayed different neurophysiological phenotypes and a very low prevalence of NP. LEPs were normal in all but one CMTX1 patients, although lower limbs N2‐P2 amplitude was significantly reduced in males ( p = 0.043). MFN2‐CMTs were NP free and LEPs recordings were all normal. NP strictly correlated with LEPs alterations ( p = 0.017). Conclusions: NP prevalence varies among CMTs subtypes and is mainly related to Aδ fibers impairment. Significance: Neuropathic pain is a frequent finding in Charcot–Marie Tooth disease and is related to Aδ fibers impairment. Patients at higher risk are those belonging to certain genetic subtypes (i.e. CMT1A and CMT2J) or with laser‐evoked potentials abnormalities. While managing this disease, clinicians should be aware of this symptom in order to offer best treatment options to their patients.